The Multidimensional Impact of Artificial Intelligence on the Job Market and Infrastructure: Focusing on Employment Shifts and Smart Libraries - Zhang, Jingyi (Journal of Computer, Signal, and System Research, 2025)
The rapid development of artificial intelligence (AI) is transforming the job market and infrastructure, bringing both opportunities and challenges. This paper examines AI’s multidimensional impact by combining literature review and empirical research. It first explores the evolution of AI technology and its key drivers, laying the groundwork for assessing its broader implications. The study then analyzes AI’s effects on the job market, focusing on mechanisms of job displacement, transformation, and creation, supported by a regression model to quantify employment trends. Furthermore, it investigates AI’s role in higher education infrastructure, using university libraries as an example to illustrate how AI enhances library automation, resource management, and personalized services. The findings indicate that AI’s impact is highly sector-specific and influenced by automation intensity, workforce adaptability, and institutional policies. The paper concludes with policy recommendations emphasizing reskilling programs, ethical AI governance, and strategies for sustainable AI integration in education and employment sectors.